1996
DOI: 10.1093/oxfordjournals.humrep.a019457
|View full text |Cite
|
Sign up to set email alerts
|

Endocrinology: Prevention of irreversible chemotherapy-induced ovarian damage in young women with lymphoma by a gonadotrophin-releasing hormone agonist in parallel to chemotherapy

Abstract: To examine whether the concomitant administration of a gonadotrophin-releasing hormone agonist (GnRHa) during combination chemotherapy to young women with lymphoma may facilitate preservation of gonadal function, a prospective clinical protocol was undertaken in 18 cycling women with lymphoma, aged 15-40 years. Thirteen patients suffered from Hodgkin disease (HD) and 5 from non-Hodgkin lymphoma. After informed consent a monthly injection of depot D-TRP6-GnRHa was administered for a maximum of 6 months starting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
95
0
10

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(109 citation statements)
references
References 8 publications
4
95
0
10
Order By: Relevance
“…Further trials are needed to validate clinical potential of GnRH in the preservation of fertility. [17][18][19][20] In spite of the fact that almost all women who undergo BMT have developed an ovarian failure, recovery is possible. A large retrospective survey of fertility after SCT involving 37 362 patients revealed that only 0.6% of patients conceived after one autologous or allogeneic SCT.…”
Section: Discussionmentioning
confidence: 99%
“…Further trials are needed to validate clinical potential of GnRH in the preservation of fertility. [17][18][19][20] In spite of the fact that almost all women who undergo BMT have developed an ovarian failure, recovery is possible. A large retrospective survey of fertility after SCT involving 37 362 patients revealed that only 0.6% of patients conceived after one autologous or allogeneic SCT.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent mouse study, ovarian suppression by either a GnRHa or oral contraceptive did not prove effective against cyclophosphamide-induced ovarian damage [60]. There is a limited number of prospective studies in humans, which are flawed because of short-term follow-up and/or because of a lack of control subjects [61][62][63][64].…”
Section: Is There a Protective Role Of Gnrh Analogues Against Chemothmentioning
confidence: 99%
“…There was no control group. Blumenfeld et al [61] administered a GnRHa concurrently with chemotherapy in 18 women with Hodgkin's or non-Hodgkin's lymphomas. The study group was compared with a historical control group of 18 women treated with similar regimens.…”
Section: Is There a Protective Role Of Gnrh Analogues Against Chemothmentioning
confidence: 99%
“…Dentre as opções propostas com esta fi nalidade estão os contraceptivos hormonais combinados 2 , aqueles com progesterona exclusiva 48 e os análogos do GnRH 49 . Os contraceptivos não foram efi cazes em diminuir a incidência de falência ovariana 2,48 , provavelmente porque o efeito supressor dos contraceptivos não promove bloqueio completo do eixo hipotálamo-hipofi sário, havendo recrutamento folicular no ová-rio sem dominância folicular e ovulação 50 .…”
Section: Ooforopexiaunclassified
“…Já os análogos do GnRH têm seus resultados controversos. Blummenfeld et al 49 encorajam a utilização desta droga após encontrarem redução de 61 (11/18) para 6,7% (15/16) na incidência de falência ovariana no grupo de pacientes que receberam o análogo simultaneamente à quimioterapia comparado com pacientes que não receberam a droga; entretanto, estes dados não foram confi rmados por nenhum outro autor, nem em estudos retrospectivos, nem em trabalhos prospectivos de pequena casuística 3 . Atualmente em nosso serviço o acetato de leuprolide vem sendo utilizado rotineiramente durante a quimioterapia em pacientes com cânceres hematológicos, com fi nalidade de produzir amenorréia e evitar o sangramento menstrual, que costuma ser abundante devido à plaquetopenia secundária à quimioterapia.…”
Section: Ooforopexiaunclassified